2002
DOI: 10.1097/00000478-200210000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Lymphomas With Prominent Granulomatous Reaction

Abstract: The presence of a granulomatous reaction in lesions of cutaneous lymphomas has been described in the past in several cases. Especially in mycosis fungoides, a "granulomatous" variant of the disease has been well characterized. We studied the clinicopathologic features of cutaneous lymphomas with prominent granulomatous reaction, including both cutaneous T-cell lymphomas and B-cell lymphomas (primary cutaneous lymphoma 22, secondary cutaneous lymphoma one). Biopsies of 23 patients with histopathologic features … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 145 publications
(25 citation statements)
references
References 53 publications
0
25
0
Order By: Relevance
“…12,14 The presence of eosinophils and epithelioid cell granulomas also favors CLH because they are infrequently observed in cutaneous B-cell lymphoma (CBCL). 7,16,17 Absence of clonality, as demonstrated by polyclonal K and L light chain stains and negative TCR and immunoglobulin heavy (IgH) gene rearrangements studies, are also considered to be supportive of CLH. 3,6,7 None of the aforementioned criteria, however, is discriminative by itself, and the diagnosis is based on a constellation of several findings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…12,14 The presence of eosinophils and epithelioid cell granulomas also favors CLH because they are infrequently observed in cutaneous B-cell lymphoma (CBCL). 7,16,17 Absence of clonality, as demonstrated by polyclonal K and L light chain stains and negative TCR and immunoglobulin heavy (IgH) gene rearrangements studies, are also considered to be supportive of CLH. 3,6,7 None of the aforementioned criteria, however, is discriminative by itself, and the diagnosis is based on a constellation of several findings.…”
Section: Discussionmentioning
confidence: 99%
“…14,18 The presence of eosinophils and clusters of epithelioid histiocytes may be helpful in the differential diagnosis because they are less frequently observed in CBCL. 7,16,17 Negative gene rearrangement studies are usually supportive of CLH, although there are rare reported cases that progressed into cutaneous lymphoma despite the lack of clonality. 15 The remaining 8 CLH cases in our series did not reveal GC clusters, although in 2 cases there were 1 or more small aggregates of blast-like B cells that failed to stain for any of the GC markers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Up to now, 39 cases have been reported in the literature [6, 7, 8, 9, 10, 11]. In this article, we present a new case; the clinical, histological, immunohistochemical and ultrastructural results and genetic studies are discussed as well as the molecular biology.…”
Section: Introductionmentioning
confidence: 89%
“…PCR analysis of the T-cell receptor γ gene was performed in 24 cases according to standard procedures as described previously with minor modifications [10]. …”
Section: Methodsmentioning
confidence: 99%